2014
DOI: 10.1002/ejhf.171
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐dependent regulation of fibrosis and inflammation in human left ventricular remodelling under pressure overload

Abstract: AimsWomen with aortic stenosis develop a more concentric form of LV hypertrophy than men. However, the molecular factors underlying sex differences in LV remodelling are incompletely understood. We took an unbiased approach to identify sex-specific patterns in gene expression and pathway regulation, and confirmed the most prominent findings in human hearts. Methods and resultsEchocardiography was performed in 104 patients (53.8% women) with aortic stenosis before aortic valve replacement. LV mass, LV end-dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 40 publications
5
119
1
1
Order By: Relevance
“…/e' = average mitral E-wave to annulus e'-wave ratio; EOA = effective prosthesis orifice area; EOAi = indexed EOA; ELI = energy loss index; LA = left atrium; LV = left ventricular; ns = non-significant; NYHA = New York Heart Association functional class; Zva = valvuloarterial impedance.F I G U R E 3 Sex distribution of prosthesis size has an alleged role. However, it is interesting to recall that sex differences in collagen architecture have already been reported in human AS 40 as well as sex regulation of fibrosis in human LV remodeling in states of pressure overload 41. Estimated GFR was lower in our females, but we did not confirm the correlation between moderate reduction of estimated GFR and increase in LVM/height 2.Table 3), that was reported in hypertensive patients.…”
contrasting
confidence: 62%
“…/e' = average mitral E-wave to annulus e'-wave ratio; EOA = effective prosthesis orifice area; EOAi = indexed EOA; ELI = energy loss index; LA = left atrium; LV = left ventricular; ns = non-significant; NYHA = New York Heart Association functional class; Zva = valvuloarterial impedance.F I G U R E 3 Sex distribution of prosthesis size has an alleged role. However, it is interesting to recall that sex differences in collagen architecture have already been reported in human AS 40 as well as sex regulation of fibrosis in human LV remodeling in states of pressure overload 41. Estimated GFR was lower in our females, but we did not confirm the correlation between moderate reduction of estimated GFR and increase in LVM/height 2.Table 3), that was reported in hypertensive patients.…”
contrasting
confidence: 62%
“…Many of these differences were on sex chromosomes. Kararigas et al reported sex‐dependent differences in transcripts in fibrosis and inflammation pathways in human pressure overload hypertrophy. Fermin et al studied dilated cardiomyopathy in 30 female and 72 male patients and reported 1800 genes showing a sex difference, including genes in ion transport and G‐protein–coupled receptor pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The array was scanned in a GeneChip Scanner 3000. The computational and statistical analysis of the microarray data was carried out using R version 2.14.2 software and the Bioconductor packages 21 as described recently 22, 23 . Following background correction, expression data were normalized with the variance stabilization and normalization algorithm 24 and log 2 transformed using the median polish algorithm of robust multi-array average 25 .…”
Section: Methodsmentioning
confidence: 99%